Neuro-ophthalmologic evaluation, quality of life, and functional disability in patients with MS - Garcia-Martin, Elena; Rodriguez-Mena, Diego; Herrero, Raquel; Almarcegui, Carmen; Dolz, Isabel; Martin, Jesus; Ara, Jose R; Larrosa, Jose M; Polo, Vicente; Fernández, Javier; Pablo, Luis E (Neurology, 2013)
To evaluate correlations between longitudinal changes in neuro-ophthalmologic measures and quality of life (QOL) and disability in patients with multiple sclerosis (MS), using optical coherence tomography (OCT), visual evoked potentials (VEP), and visual field examination. Fifty-four patients with relapsing-remitting MS were enrolled in this study and underwent Multiple Sclerosis Quality of Life questionnaire (54 items) (MSQOL-54) and Expanded Disability Status Scale (EDSS) evaluation, as well as complete neuro-ophthalmologic examination including visual field testing and retinal nerve fiber layer (RNFL) measurements using Cirrus and Spectralis OCT and VEP. All patients were re-evaluated at 12, 24, and 36 months. Logistical regression was performed to analyze which measures, if any, could predict QOL. Overall, RNFL thickness results at the baseline evaluation were significantly different from those at 3 years (p ≤ 0.05), but there were no differences in functional measures (visual acuity, contrast sensitivity, color vision, visual field, and VEP). A reduced MSQOL-54 score was associated with an increase in EDSS score and a decrease in both functional and structural parameters. Patients with longer MS duration presented with a lower MSQOL-54 score (reduction in QOL). Patients with progressive axonal loss as seen in RNFL results had a lower QOL and more functional disability.